Climate change in East and Central Asia associated with the uplift of the Tibetan Plateau–A simulation with the MRI coupled atmosphere-ocean GCM - Abe, Manabu; Yasunari, Tetsuzo; Kitoh, Akio (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 p.85-6